Akulturasi Islam Nusantara Membawa Peradaban Budaya dan Agama - Taufik usman; Sam’un Mukraimin; Fatimah Azis (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Islam Nusantara is a model of thought, understanding and practice of Islamic teachings packaged through considerations of culture or traditions that developed in the Southeast Asian region (but this study is limited to Indonesia), thus reflecting a methodological nuanced Islamic identity. When this identity was disseminated among Muslims, especially its thinkers, it was responded with controversial responses: some rejected the Islamic Nusantara identity because there was only one Islam, namely Islam taught by the Prophet. On the other hand, many Islamic thinkers who accept Islamic identity cannot be separated from that, Islam Nusantara is a part of acculturation as a carrier of Islamic teachings through the acculturation of existing cultures so that Islam Nusantara is present, none other than to broadcast the Islamic religion through peace between culture and religion.